Migrant capital: examining the production of the industrial landscape of the [Delhi] National Capital Region, India - Mishra, S (2021)
I argue that the Delhi National Capital Region is emerging as a “migrant capital as it is fed by an increasingly migrant workforce in the manufacturing sector. In context of informalisation of work globally and deregulation of labour in India, I compare employment relations in a deregulated (the Special Economic Zone or SEZ in Noida) space with regulated spaces (the larger industrial region, non-SEZ), across two distinct sectors, low-skilled garment manufacturing units and high-skilled electronics manufacturing units. I also examine one Chinese owned and managed factory and resulting employment relations in the high-skilled sector between Chinese and Indian nationals. I analyse the industrial relations that arise because of interactions between a largely migrant workforce and their locally rooted employers. Employers embedded in local networks of power can create hybrid forms of regulation to adapt formal laws into informal practices across deregulated and regulated spaces, creating similar conditions in both irrespective of law. Even Chinese managers rely on the networks of locally embedded Indian managers to manage their migrant workforce through informal practices. Hybrid regulation is made possible due to a migrant workforce that lacks access to local informal networks of power being dis-embedded from local society. In the absence of effective formal legal protection, migrants adapt to rather than challenge the system of hybrid regulation through a variety of informal means. Using an embedded qualitative framework and ethnographic methods, I use the analytical tool of inter-regional migration and the category of the “local" to understand the dynamics of industrial relations that create spaces for an adaptation of formal law into informal practices. My thesis contributes by linking an informality of work that migrants experience as workers inside factories with an informality of life which they experience as outsiders in the city.